Prediction of LED luminaire spectral power distribution using a mathematical model developed based on interpolation method - Sikora, Roman; Markiewicz, Przemysław; Pawlak, Andrzej (Photonics Letters of Poland, 2022)
LED luminaires with controllable luminous flux are increasingly used, mainly due to the need to reduce electricity consumption, which is the equivalent of improving the energy efficiency of a lighting installation. Changing the dimming level changes the spectral power distribution of the luminaire or light source. Knowledge of dimming characteristics including spectral power distribution relationships provides the opportunity to optimize control algorithms and predict the impact of lighting parameters on the work surface. The paper presents a mathematical model to calculate the spectral power distribution of an LED luminaire for any level of dimming. Two interpolation methods were used to develop the model, fitted by polynomial functions and spline functions. Validation of the model was performed for two values of control voltage-dimming levels. Full Text: PDF References J. Silva, J.F.G. Mendes, L.T. Silva, "Assessment Of Energy Efficiency In Street Lighting Design", WIT Transaction on Ecology and the Environment 129, 705 (2010). CrossRef A. Nardelli, E. Deuschle, L.Dalpaz de Azevedo, J. Lorenço Novaes Pessoa, E. Ghisi, "Assessment of Light Emitting Diodes technology for general lighting: A critical review", Renewable and Sustainable Energy Rev. 75, 368 (2017). CrossRef O. Rabaza, D. Gómez-Lorente, F. Pérez-Ocón, A. Peña-García, "A simple and accurate model for the design of public lighting with energy efficiency functions based on regression analysis", Energy 107, 831 (2016). CrossRef S. Raggiunto, A. Belli, L. Palma, P. Ceregioli, M. Gattari, P. Pierleoni, "An Efficient Method for LED Light Sources Characterization", Electronics 8(10), 1089 (2019). CrossRef I. Rachev, T. Djamiykov, M. Marinov, N. Hinov, "Improvement of the Approximation Accuracy of LED Radiation Patterns", Electronics 8, 337 (2019). CrossRef